Implementasi Pembelajaran Pai Kelas X Berbasis Adiwiyata - Inayah Wardah K; Umi Hanik; Alfin Khasanah (Tarbawi : Jurnal Studi Pendidikan Islami, 2023)
The main aim of this research is to describe the implementation of Adiwiyata-based Islamic religious education learning at SMA Negeri 3 Pasuruan. The research method uses a qualitative research approach with descriptive research type. This research was carried out at SMA Negeri 3 Pasuruan. The data sources in this research are Islamic Religious Education subject teachers and students. Data collection techniques use observation, interviews and documentation. The results of the research are that the implementation of the Adiwiyata program has been implemented well and is in accordance with Adiwiyata school standards according to the criteria of the Ministry of the Environment and the behavior of most school residents has good criteria in school environmental management activities. Based on observations that have been made, students at SMAN 3 PASURUAN basically have the character of caring about the environment, such as always maintaining cleanliness, taking off their shoes when entering class, using ablution water sufficiently and not excessively, so that the arguments from the Qur'an or The hadith regarding environmental awareness has been widely applied, both through subject matter and through the practice of daily life.